Relatório de Estágio Profissional "Feliz aquele que transfere aquilo que sabe e aprende o que ensina" - Ana Rita Pereira Vieira (2017)
The year of professional internship is the experience of all previous academic education, where the student put to the test by being confronted with reality. It is in this meeting that the trainee teacher, will put into practice a whole theory heard until then, giving meaning to everything that has been learned. The year of professional internship is characterized by the diversity of experiences encountered and the transition from theory to practice, but that only ends with the internship report. This document consists in a summary of reflections about personal and professional experiences on what was developed during the internship year. This report summarizes the process of transformation of a trainee student, who happened in the Secondary School of Penafiel. It is organized into seven distinct chapters: (1) the introduction, where the purpose of document is described; (2) the personal dimension in which one describes a personal aspect of the trainee student and her history with the sport; (3) the institutional dimension, where the context of the internship is characterized; (4) planning to improve achievement, where different levels of planning are defined and how they were implemented during this school year; (5) from theory to practice, where the whole process of classroom management, teaching models, instruction and pedagogical feedback, assessment, observations and logbooks are referenced and explained; (6) the research study, entitled "Impact of the use of a teacher-centered teaching model and a student-centered teaching model on the level of student motivation in the dance didactic unit"; (7) to live in the environment in which one lives, in which coexistence with the school community in the year of internship is described; (8) future perspectives, where was made a general reflection of the year of internship and its importance; (9) bibliographical references and annexes, respectively. KEYWORDS: PROFESSIONAL